The role of Tat in HIV latency and reactivation - Margolis, David M.; Browne, Edward P. (Frontiers in Immunology, 2025)
HIV persists during therapy due the existence of a latently infected reservoir in which viral gene expression is silenced. This reservoir thus represents the primary barrier to a cure for HIV. To eliminate latently infected cells from people with HIV (PWH) on antiretroviral therapy (ART), small molecules that reverse HIV latency (Latency reversing agents – LRAs) have been previously developed and tested, but these lack specificity for HIV and are typically inefficient at promoting broad reservoir reactivation. As such, more potent and selective tools for latency reversal are needed. Recently, delivery of mRNA encoding the viral protein Tat, which promotes transcriptional elongation, has attracted interest as a possible HIV-specific approach to inducing latency reversal. This review will cover the evidence that Tat plays a key role in both establishment of HIV latency and latency reversal, as well as recent developments in which Tat mRNA delivery has been used to enhance latency reversal approaches. Delivery of Tat to infected cells represents a promising avenue to bypass the limitations of small molecule LRAs and achieve broad reactivation of the clinical reservoir.